Psychosocial Care Network (RAPS) and the recursion of care in the territory: family health strategy team of the municipality of Guaratuba/PR (Research, Society and Development, 2022)
The Psychosocial Care Network (RAPS) is a thematic health network, which involves care, aiming to ensure that people with mental suffering and with needs arising from drug use have access to comprehensive, continuous care and linkage to the network. The research aims to investigate how the actions of territorial and community-based services focused on mental health, with the participation of the RAPS, more specifically of the family health strategy teams, are happening in the municipality of Guaratuba/PR. A descriptive, exploratory study with a qualitative approach was elaborated, where the qualitative data collected through semi-structured interviews with doctors and nurses from the seven (07) Basic Health Units in the city of Guaratuba, with eighteen (18) individual interviews and five (05) focus groups with Community Health Agents (CHA). The collected data were entered into the N-VIVO software, which supported the coding and analysis of the categories. All information was compiled and analyzed using the literature on Sustainable Territorial Development and legislation in the area of ​​Public Mental Health Policies. This research was approved by the Research Ethics Committee of UFPR/SCS in December 2020, CAAE 39730220.9.0000.0102, with opinion number 4,465,459.